Dinamika Keluarga Kristen di Era Gaya Hidup Modern: Kajian Pastoral Konseling di Jemaat GKII Efata Bonet Engkabang Sungai Tebelian - Yefen Benhur Lifiar Utan (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the dynamics of Christian families in navigating modern lifestyles, focusing on the congregation of GKII Efata Bonet Engkabang. Modernity characterized by digitalization, high mobility, economic pressure, and shifting social values has significantly influenced family communication patterns, emotional relationships, and spiritual formation within Christian households. The purpose of this study is to describe the changes experienced by congregational families in the context of modernity and to analyze the role of pastoral counseling as a relevant form of support for family well-being. This research employed a descriptive qualitative method, collecting data through in-depth interviews, limited observations, and a review of church documents. The findings indicate that Christian families face challenges such as declining communication quality, reduced family time, the pervasive influence of gadgets on daily interactions, and weakened spiritual disciplines. Furthermore, shifting parenting patterns and increasing psychological pressure also affect family stability. Within this context, pastoral counseling in GKII Efata Bonet Engkabang plays an essential role in providing spiritual, emotional, and practical guidance through empathetic, relational, and faith-based approaches. Pastoral care has proven effective in helping families realign life priorities, strengthen communication, and cultivate sustainable spiritual practices. The implications of this study highlight the urgency of enhancing structured family support programs in the church, improving pastoral leaders’ capacity as counselors, and encouraging families to develop healthy digital discipline to maintain relational and spiritual quality amid the demands of modern life.